What about the independence of investigative journalism centers in Malawi - Ziba, Muyanga (Revue internationale Animation, territoires et pratiques socioculturelles / International Journal of Sociocultural community development and practices / Revista internacional Animación, territorios y prácticas socioculturales)

(untitled) (Département de communication sociale et publique, Université du Québec à Montréal, 2026)
Investigative journalism has brought advantages and challenges in Malawi. Centres for journalism have revealed that even in the media there is corruption. These centres do not have financial independence although they have editorial independence and hence can only carry work that does not require a lot of expenses. Based on two cases, namely Centre for investigative journalism and Investigative Journalism Platform, the study used qualitative approach that included semi-structured interviews. It was guided by the following question: to what extend are investigative journalism centres independent? The results disclosed that some institutions are supported while others are not hampering the process of investigative journalism. They showed that governments and security agents do not have much influence on the way information is gathered.